SOCIALY RESPONSIBLE MARKETING - YESTERDAY AND TODAY - Ilic, Milena; Radnovic, Branislav; D. Zivkovic, Zoran (Journal of Economic Development, Environment and People, 2012)
Several factors direct the companies to apply a higher level of corporate social responsibility: the increasing expectations of customers, changes in expectations of employees, laws and government pressure, investor interest in the social criteria and changes in supply practices The basic principles of socially responsible marketing as an ethical business, respect for ecological principles and respect for the legislation. Organizations must ensure that all employees know and observe the relevant laws. Companies must adopt and make available to the written rules of ethics, to develop tradition of ethical conduct in the company and impose a responsibility to his men to follow ethical and legal guidelines. By adopting these or similar principles, companies can create opportunities to reduce current and future costs, strengthen competitiveness and market position and achieving greater profits. In contemporary business, more ecological component is present in the execution of business activities as an important prerequisite for improving competitive advantage and company image. Awareness of the issue of environmental protection in companies has evolved primarily as a result of the influence of customers and various non-governmental and non-profit organizations on marketing orientation of companies, and the requirements for the development of products and services that meet environmental standards and consumer needs.